Estimating irrigation demand using satellite remote sensing : a case study of Paphos district area in Cyprus - Papadavid, George; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2008)
The monitoring of agricultural areas in Cyprus provides important data for efficient water supply plans and for avoiding unnecessary water lost due to inefficient irrigation. In this context, satellite remote sensing techniques may be useful as an efficient tool for monitoring agricultural areas. The objective of this study is to present the overall methodology for monitoring agricultural areas and estimating the irrigation demand in Cyprus using satellite remote sensing, irrigation models and other auxiliary data. Field spectro-radiometric measurements using SVC-HR 1024 and GER 1500 were undertaken to determine the spectral signature of different types of crops so as to assist our classification techniques. Final crop maps using Landsat TM and ETM+ can be produced and the optimal amount of irrigation demand required for certain types of crops can be determined in order to avoid any non-effective water management. This paper presents the overall methodology of the proposed research study designed to enable the implementation of an integrated approach by combining satellite remote sensing, irrigation models, micro-sensor technology and in-situ spectroradiometric measurements to determine the irrigation demand and finally to validate our results
Keywords: Irrigation; Hydrology; Mathematical models; Remote sensing; Satellites; Water--Management